(untitled) (Journal of Economic Research & Business Administration, 2017)
Article purpose – developing a model of an assessment of real cost of construction projects on the basis of the analysis of state regulation’s mechanisms of housing construction sector. The methods of statistical groups, correlation and regression, economic-mathematical modeling were used for receiving results. The practical value of research is caused by that its methodical development and concrete recommendations can be used by the construction enterprises. The optimizing – econometric model of an assessment of real cost of the construction project within a state program is developed. The optimizing econometric model will give opportunity to consider a real price, so that the construction companies could exactly forecast expenditure for building. The financial expenses necessary for each of types of objects of affordable housing are considering as random variables. The state tariffs have the fixed character and established by studying of the average data and endogenous factors characterizing separate construction projects. Nevertheless, the real prices by each type of housing have floating character and change depending on change of inflation, demand for certain types of housing, etc. In this regard the question of an assessment of a deviation of the real prices from the tariff prices is actual. Such problem definition allows to determine the real maximum quantity of affordable housing by each of types and to distribute resources in the best way.